The Effect of Resource-based View on Dive Trip Operators on Their Reputation and Its Impact on Dive Tourists’ Trust in Indonesia - Jilmi Astina Anif; Ernie Tisnawati Sule; Hilmiana Yudo Martono; Sucherly Sucherly (Journal of International Conference Proceedings (JICP), 2019)
As a country with the second longest coastline in the world, Indonesia has vast potential for marine tourism. Dive tourism, in particular, is one of the growing marine tourism in the archipelago. The aim of this research is to analyze the RBV (resourcebased view) effect on the reputation of dive trip operators as well as its impact to tourists’ trust in Indonesia. The method employed in this research is the variable- or componentbased structural equation modelling (SEM), which is the PLS (partial least square), to verify the connection between variables. The result shows that RBV affects tourists’ trust through the reputation of dive trip operators. However, RBC does not directly affect the trust.